Determination of Helicobacter pylori antigen in adults in low socio-economic conditions in a neighborhood of Juigalpa (Revista Torreón Universitario, 2022)
Helicobacter pylori, is a negative gram bacterium capable of surviving gastric acidity causing chronic gastritis, peptic ulcer, and gastric cancer. The techniques used for the detection of this bacterium are divided into invasive and non-invasive, which provide a reliable diagnosis for the population, (Cruz, Guillén, & Martínez, 2015, p. 15)The research was quantitative, descriptive, and cross-sectional. The objective of the study was to determine H pylori infection in adults in low socio-economic conditions aged 18 to 45 years in the San Antonio neighborhood of Juigalpa.  The sample was 29 participants, to whom a questionnaire and the immunochromatographic test for the detection of the antigen of the bacterium were applied. The information was processed in SPSS v.21.The results found were: 65.5% of positive cases, overcrowding in 44.8%, and 37.9% had no knowledge about the bacteria, 100% used to eat food outside the home and 93.1% had good hygienic-eating habits at home.  When associating the symptoms with the presence of H. pylori antigen, a predominance of symptomatic infection was evidenced between 26.3 and 78.9%, except for heartburn in 100%.In short, H. pylori infection is and will continue to be one of the most frequent health problems. Ignorance about the infection and food outside the home plays a fundamental role in the acquisition of it.  Using diagnostic methodologies such as that applied in this investigation can allow the more global monitoring of the infection, both in symptomatic and asymptomatic patients.
Keywords: adult; antigen; determination; Helicobacter pylori; immunochromatography